'Meal-sharing' platforms: a boon or bane for restaurants?. Issue 20 (18th October 2022) - Mhlanga, Oswald
ABSTRACT: Despite the growing literature on the sharing economy in the tourism and hospitality sector particularly in the context of car sharing, and accommodation sharing, research in other emerging domains of the sharing economy is lacking. The present study seeks to add knowledge in this area, by exploring the impacts of the sharing economy, in the food domain, on incumbent firms. Using two cities in South Africa, the study measures the impacts of meal-sharing platforms, which are apps for home restaurants, on restaurant performances. A difference-in-difference model was estimated using a population-based dataset of 467 restaurants from 2016 to 2018. Several robustness checks were carried out on the variables to avoid spurious results. The findings reveal that meal-sharing platforms significantly ( p  < 0.05) and negatively impacts on restaurant customers and has a non-significant impact on meal prices and restaurant revenue. An analysis of the impact across restaurant categories reveals that the impact is non-uniform, with restaurants catering to budget diners being the most affected. However, due to the nature of the restaurant service, the study concludes that meal-sharing platforms are not a disruptive innovation to the restaurant industry. A true meal in any self-respecting restaurant is tech-free, engaging, authentic and sensory.